Teologi Inkulturasi dalam Sejarah Gereja dan Dewasa Ini di Flores, Indonesia - Georg Ludwig Kirchberger (Institut Filsafat dan Teknologi Kreatif Ledalero, 2023)
This article is based on a book by Emanuel Martasudjita on Inculturation Theology. The author of this article supports thestatement of E. Martasudjita that inculturation of theology is not a new reality, but has been known and practicedthroughout the history of the Church. By expanding on the description given by Martasudjita regarding the stages in thedevelopment of history, the author of the article draws on the basic insight from that history that inculturated theology is notconstructed, but must grow in the reflections made by the faithful about their Christian faith, where they use the way ofthinking, they have according to the culture they live in.From the research on history, it is learned that changes in form in theology often occur based on different favorite ideasheld by different cultures, besides that there has also been the formation of new theology, where people with certain culturalbackgrounds learn theology from other cultures. In this case it is easy to misunderstand which can trigger a long discussionthat results in a new form of expression of the Christian faith.By taking the results of this historical research, the author highlights the situation of practice of faith and reflection of faithin the Flores island in South East Indonesia.Keywords: Inculturation, history of theology, local culture in Flores, Basic Ecclesial Communities